MENINGKATKAN HASIL BELAJAR EKONOMI MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Salmi Salmi (Universitas Negeri Medan, 2018)
Abstract: Increasing Economic Learning Outcomes Through Problem BasedLearning Learning Models. This study aims to determine the process of economiclearning in SMA Negeri 13 with Problem Based Learning (PBL) learning models, itcan increase the activeness of students so that they can improve the learningoutcomes of economics for students of class X.IPS.2 Palembang State High School13. The research used was Classroom Action Research (CAR) or Classroom ActionResearch (CAR). In this study there are several cycles. Each cycle consists of 4stages of interrelated and continuous activities, namely: planning, acting, observingand reflecting. The subjects referred to actions in this study were students of class XIPS. 2 Palembang 13 State Senior High Schools totaling 40 students. Data collectiontechniques use tests and observations. The results of this study indicate that byapplying the Problem Based Learning (PBL) learning model the learning outcomesof students can be seen from the results before the action is taken and after the actionis taken, namely; cycle I (65%), and cycle II (92.50%). Means there is an increase instudent learning outcomes and learning process activities of students after classaction research.Keywords: Economy, Problem Based LearningAbstrak: Meningkatkan Hasil Belajar Ekonomi Melalui ModelPembelajaran Problem Based Learning . Penelitian ini bertujuan untukmengetahui proses pembelajaran ekonomi di SMA Negeri 13 Palembang denganmodel pembelajaran Problem Based Learning (PBL), dapat meningkatkan keaktifanpeserta didik sehingga dapat meningkatkan hasil belajar ekonomi pada peserta didikkelas X.IPS.2 SMA Negeri 13 Palembang. Penelitian yang digunakan adalahPenelitian Tindakan Kelas (PTK) atau Classroom Action Research (CAR). Dalampenelitian ini terdapat beberapa siklus. Setiap siklus terdiri atas 4 tahap kegiatanyang saling terkait dan berkesinambungan yaitu: perencanaan tindakan (planning),pelaksanaan tindakan (acting), pengamatan (observing) dan refleksi (reflecting).Subjek yang dimaksud tindakan dalams penelitian ini adalah peserta didik kelas XIPS.2 SMA Negeri 13 Palembang yang berjumlah 40 peserta didik. Teknikpengumpulan data menggunakan tes dan observasi. Hasil penelitian inimenunjukkan dengan menerapkan model pembelajaran Problem Based Learning(PBL) hasil belajar peserta didik meningkat dapat dilihat dari hasil sebelumdilakukan tindakan dan sesudah dilakukan tindakan yaitu; siklus I (65%), dan siklusII (92.50%). Berarti terdapat peningkatan hasil belajar peserta didik dan aktivitasproses pembelajaran para peserta didik setelah dilakukan penelitian tindakan kelas.Kata Kunci : Ekonomi, Problem Based Learning